Electro-Acupuncture Promotes the Differentiation of Endogenous Neural Stem Cells via Exosomal microRNA 146b After Ischemic Stroke - Zhang, Shenghang; Jin, Tingting; Wang, Lulu; Liu, Weilin; Zhang, Yuhao; Zheng, Yi; Lin, Yunjiao; Yang, Minguang; He, Xiaojun; Lin, Huawei; Chen, Lidian; Tao, Jing (Frontiers in Cellular Neuroscience, 2020)
Background: Evidences indicate that exosomes-mediated delivery of microRNAs (miRNAs or miRs) is involved in the neurogenesis of stroke. This study was to investigate the role of exosomal miRNAs in non-drug therapy of electro-acupuncture (EA) regulating endogenous neural stem cells for stroke recovery. Methods: The model of focal cerebral ischemia and reperfusion in rats were established by middle cerebral artery occlusion (MCAO) and treated by EA. The exosomes were extracted from peri-ischemic striatum and identified by exosomal biomarkers, and detected differentially expressed miRNAs with microarray chip. Primary stem cells were cultured, and oxygen–glucose deprivation and reperfusion (OGD/R) was used to mimic vitro ischemic injury. Results: The levels of exosomal biomarkers TSG101 and CD81 were increased in peri-ischemic striatum after EA treatment, and we revealed 25 differentially expressed miRNAs in isolated exosomes, of which miR-146b was selected for further analysis, and demonstrated that EA increased miR-146b expression and its inhibitors could block the effects. Subsequently, we confirmed that EA upregulated miR-146b expression to promote neural stem cells differentiation into neurons in peri-ischemic striatum. In vitro, it was verified that OGD/R hindered neural stem cells differentiation, and miR-146b inhibitors furtherly suppressed its differentiation, simultaneously NeuroD1 was involved in neural stem cells differentiation into neurons. Moreover, in vivo we found EA promoted NeuroD1-mediated neural stem cells differentiation via miR-146b. In addition, EA also could improve neurological deficits through miR-146b after ischemic stroke. Conclusion: EA promotes the differentiation of endogenous neural stem cells via exosomal miR-146b to improve neurological injury after ischemic stroke.